The Influence of Syriac Bible Commentaries on Judeo Arabic Exegesis as Demonstrated by Several Stories from the Book of Genesis - Zoref, Arye (Studies in Christian-Jewish Relations, 2016)
The article examines the influence of Syriac biblical commentaries on Judeo Arabic biblical exegesis through the lens provided by several stories from Genesis. In the story of the sons of God (Genesis 6), Judeo Arabic commentators adopted the Syriac view that the sons of God were the descendants of Seth. In the story of Nimrod, Judeo Arabic commentators adopted the positive view of the Syriac commentaries regarding Nimrod. As part of this examination the article explores the techniques used by Judeo Arabic commentators to incorporate Syriac materials into their commentaries, and in particular focuses on the treatment of the Syriac materials by three Judeo Arabic commentators: Qirqisani, Yefet b. 'Ali and Yeshu'ah b. Yehuda.